Efektivitas Media Batang Napier Untuk Meningkatkan Hasil Belajar Peserta Didik Pada Pembelajaran Operasi Perkalian Bilangan Cacah Kelas V SD N 1 Cening - Muhamad Najah Ilham Albasir; Eka Titi Andaryani (De Fermat : Jurnal Pendidikan Matematika, 2026)
This research is motivated by the low multiplication skills among fifth-grade students, a subject often perceived as daunting. This study aims to determine the effect of using Napier’s Bones media on mathematics learning outcomes at SD Negeri 01 Cening. A quasi-experimental method was employed, involving class V A as the experimental group and class V B as the control group. The hypothesis test results revealed an Asymp. Sig. (2-tailed) value of 0.000 (p < 0.05). Furthermore, the mean score of the experimental group reached (61.25), significantly higher than the control group which only obtained (40.). These findings provide strong statistical evidence that the implementation of Napier’s Bones media has a significant impact on improving the mathematics learning outcomes of fifth-grade students at SD Negeri 01 Cening.